Forest Conservation and Human Security: A Qualitative Study of Forest Reserves in Ondo State, Nigeria - Ebire, Matthew Olusola; Adeniyi, Israel Ademola; Agbonifo, John (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025DO - 10.58709/niujss.v11i3.2245, 2025)
This study examines the relationship between forest conservation and human security in Ondo State, Nigeria, focusing on food security, livelihoods, socio-cultural stability, environmental sustainability, biodiversity protection, land tenure, and political security. Using qualitative methods, including focus group discussions and key informant interviews, the findings reveal that forest degradation threatens food supply, economic well-being, cultural heritage, and biodiversity, while fostering insecurity and criminal activities in forest reserves. Conversely, sustainable forest management enhances community resilience, climate stability, and poverty reduction. The study recommends participatory governance, secure land tenure, alternative livelihoods, and integration of indigenous knowledge for effective conservation and improved human security. Keywords: Forest conservation, forest management, human security, forest-adjacent communities.